2018
DOI: 10.1016/j.anifeedsci.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of corn silage with Lactobacillus plantarum and Bacillus subtilis associated with amylolytic enzyme supply at feeding. 1. Feed intake, apparent digestibility, and microbial protein synthesis in wethers

Abstract: The current study aimed to investigate the effects of corn silage inoculation and dietary supplementation with amylolytic enzymes, and their interactions, on feed intake, apparent digestibility, and microbial protein synthesis in wethers. Whole-crop corn forage was ensiled either with water (untreated) or with Lactobacillus plantarum MA 18/5U at 1 × 10 5 cfu/g fresh forage combined with Bacillus subtilis AT553098 at 1 × 10 5 cfu/g fresh forage (inoculated). Eight ruminally cannulated Dorper × Santa Inês crossb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
1
14
1
Order By: Relevance
“…Ruminal degradation of amylose and amylopectin into compounds of lower molecular weights could increase total VFA concentrations, resulting in increased FA synthesis and subsequent modifications in the FA profiles of the meat due to changes in VFA molar proportion (Church, 1993). However, in our study with wethers (Lara et al, 2018), enzyme supplementation had no effect on total VFA concentrations, whereas propionate was altered by the interaction between inoculation and enzyme supplementation, and thus no clear patterns have emerged. This explains the lack of response of FA composition to enzyme supplementation.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Ruminal degradation of amylose and amylopectin into compounds of lower molecular weights could increase total VFA concentrations, resulting in increased FA synthesis and subsequent modifications in the FA profiles of the meat due to changes in VFA molar proportion (Church, 1993). However, in our study with wethers (Lara et al, 2018), enzyme supplementation had no effect on total VFA concentrations, whereas propionate was altered by the interaction between inoculation and enzyme supplementation, and thus no clear patterns have emerged. This explains the lack of response of FA composition to enzyme supplementation.…”
Section: Discussioncontrasting
confidence: 78%
“…Notably, the results from the literature regarding the effectiveness of amylolytic enzyme supplementation are highly inconsistent, and enhanced growth performance may not be expected in most cases. Furthermore, it is worth noting that the diets used in this study had increased total-tract starch digestibility (> 96%) when fed to wethers (Lara et al, 2018). In this regard, it is unlikely that small improvements in starch digestibility caused by amylase supplementation may result in enhanced feed intake and growth performance.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The mean values of lamb meat tenderness found in the present study (3.33 kgf) are classified as soft (Tatum, Smith, & Belk, 2000). Similar result was reported by Lara, Bragiato, Rabelo, Messana, & Reis (2018), who found mean of 3.00 kgf when evaluating the meat quality of lambs fed with maize silage.…”
Section: Qualitative Characteristicssupporting
confidence: 90%
“…According to Madruga, Sousa, Rosales, Cunha, & Ramos (2005), sheep meat chemical composition consists, on average, of 75% moisture, 19% protein, 4% fat and 1% mineral matter, with possible variations in these levels depending on the age, genotype, sex, castration, pre and post-slaughter management and diet of the animal (Tshabalala, Strydom, Webb, & De Kock, 2003). He, Wu, Wang, Meng, & Zhou (2018), Campos et al (2017 and Lara et al (2018) found no differences in the chemical composition of lamb meat receiving different silages in their diets. These are similar results to those found in the present study, in which only the fat content was higher (3.23%) than those found by those previous authors.…”
Section: Centesimal Analysismentioning
confidence: 99%